CuGeO3 Nanoparticles: An Efficient Photothermal Theragnosis Agent for CT Imaging-Guided Photothermal Therapy of Cancers - Wang, Jiawu; Zhang, Chengyao (Frontiers in Bioengineering and Biotechnology, 2020)
The photothermal agents have been widely developed due to the minimally invasive treatment for targeted tumor photothermal therapy, which is considered to have great potential for antitumor bioapplications. The development of multifunctional photothermal agents shows extremely challenging. This work presents a novel photothermal theragnosis agent, i.e. CuGeO3 nanoparticles (CGO NPs), showing intense absorption in the near-infrared (NIR) window and excellent ability of CT imaging. Due to the strong NIR absorption, CGO NPs exhibit excellent photothermal effect with a photothermal conversion efficiency of 59.4%. Moreover, because of the high X-ray attenuation coefﬁcient of germanium, the CGO NPs has a great potential of CT imaging diagnosis in clinical application. Additionally, the CGO NPs shows negligible cytotoxicity in vitro and in vivo, indicating that it can be served as an outstanding contrast and anticancer agent in a biosafe way. Our work opens the way for the development of bimetallic copper-based oxides used in photothermal diagnostic agents for cancer treatment.